2013
DOI: 10.1152/ajpcell.00333.2012
|View full text |Cite
|
Sign up to set email alerts
|

Reduced adult endothelial cell EphB4 function promotes venous remodeling

Abstract: Reduced EphB4 expression is observed during vein graft adaptation and is associated with increased venous wall thickening. These findings suggest that EphB4 may mediate normal adult venous endothelial cell (EC) function and vein graft adaptation. We therefore tested the functional significance of EphB4 using EC with genetically reduced EphB4 signaling. EC were isolated from EphB4(+/+) and EphB4(+/-) mice. In vitro function was assessed through EC proliferation, migration, nitric oxide (NO) synthesis, and chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…8 Our finding that eNOS is phosphorylated with stimulation of Eph-B4 in adult venous endothelial cells is consistent with previous reports that have shown that activation of Eph-B4 enhances NO production in endothelial cells in vitro . 8, 25 We previously showed that reduced endothelial Eph-B4 signaling in endothelial cells derived from heterozygous Eph-B4 mice 27 was associated with diminished basal levels of eNOS protein expression and NO production but increased tube formation, 15 consistent with our data in vitro (Figure 3), but emphasizing the differences between endothelial cell function in vitro and in 3-dimensions, especially during vein graft adaptation in vivo .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…8 Our finding that eNOS is phosphorylated with stimulation of Eph-B4 in adult venous endothelial cells is consistent with previous reports that have shown that activation of Eph-B4 enhances NO production in endothelial cells in vitro . 8, 25 We previously showed that reduced endothelial Eph-B4 signaling in endothelial cells derived from heterozygous Eph-B4 mice 27 was associated with diminished basal levels of eNOS protein expression and NO production but increased tube formation, 15 consistent with our data in vitro (Figure 3), but emphasizing the differences between endothelial cell function in vitro and in 3-dimensions, especially during vein graft adaptation in vivo .…”
Section: Discussionsupporting
confidence: 89%
“…1922 We have previously shown that Eph-B4 expression is diminished during vein graft adaptation in adults, suggesting that successful vein graft adaptation, characterized by increased venous wall thickness and adaptive outward remodeling, is associated with loss of venous identity. 7, 8 Our data also suggests that Eph-B4 is a negative regulator of eNOS during vein graft adaptation in vivo , with reduced Eph-B4 expression during vein graft adaptation associated with enhanced eNOS phosphorylation after 3 weeks (Figure 4), although not at 1 week postoperatively, 15 consistent with successful vein graft adaptation at 3 weeks in this model. Improving vein graft adaptation with increased NO production has led to the use of eNOS as a potential therapeutic agent.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…[19][20][21][22] We have previously shown that Eph-B4 expression is diminished during vein graft adaptation in adults, suggesting that successful vein graft adaptation, characterized by increased venous wall thickness and adaptive outward remodeling, is associated with loss of venous identity. 7,8 Our data also suggests that Eph-B4 is a negative regulator of eNOS during vein graft adaptation in vivo, with reduced Eph-B4 expression during vein graft adaptation associated with enhanced eNOS phosphorylation after 3 weeks (Figure 4), although not at 1 week postoperatively, 15 consistent with successful vein graft adaptation at 3 weeks in this model. Improving vein graft adaptation with increased NO production has led to the use of eNOS as a potential therapeutic agent.…”
Section: Discussionsupporting
confidence: 74%